Molecular dynamics simulation of primary detonation process of TATB crystal under shock loading. Issue 15 (13th October 2018) - Li, Hongjian; Li, Anyang; Dou, Yusheng
Abstract: Molecular dynamics simulations were performed to gain fundamental insights into the mechanisms for the primary detonation process of 1, 3, 5-triamino-2, 4, 6-trinitrobenzene (TATB) under shock wave loading using self-consistent charge density-functional tight binding(SCC-DFTB) calculations combined with the multiscale shock technique (MSST). The primary process starts with shock loading and ends with the formation of dynamically stable heterocyclic clusters, which could inhibit the reactivity of TATB. The results show that the initial step of shocked TATB decomposition is the N–O bond cleavage; then carbon rings aggregate and connect by N atoms to form clusters; after the carbon rings open, heterocyclic clusters with nitrogen are formed, and persist throughout the simulation. This is a new mechanism for the primary processes of shocked TATB and this initiation mechanism is independent of the initial shock speeds.